“A tecnologia do corpo é o futuro!”: vestígios da potência política da dança-experiência, a partir da página Afrofunk Rio no Instagram - Carolina Souza Louback (2022)
The use of social media is a daily practice for a large part of society, configuring another contemporary public space, in which subjects interact and appear in the social scene in their own unique way. For women, in view of the impediments of different orders imposed on account of gender and race in the Brazilian context, this authorial participation in social media allows a practice of appearing within their own experiences, narrating strengths and precariousness, which were previously restricted to the intimate circle, or not even exposed among close ties out of shame or guilt. Interested in reflecting on the possibilities of women's experience in their inscriptions and in their appearance on Instagram, we focused on the profile of the Afrofunk Rio project (@afrofunkrio) to investigate the body in movement shared online – the dance-experience. The work sought to answer the following question: how does the dance-experience of Afrofunk Rio reveal itself as an important communicative gesture for the political power of women in the Brazilian context and in the context of the social network Instagram? In this sense, we developed an understanding of the terms dance-experience, communicative gesture and political power, based on different authors such as John Dewey, George-Herbert Mead and Jacques Rancière. To conceive the universe of the Afrofunk Rio project, as well as the dimension of the social network, we developed a theoretical framework based on decolonial black feminist epistemologies with the help of researchers such as Rosane Borges, Judith Butler, Maria Lugones, Lélia Gonzalez and Ângela Figueiredo. From the notion of the interactional device (BRAGA, 2020) we established the methodological procedures to analyze our corpus, which had 85 posts from March 2019 to June 2021. Our analysis highlights the figure of black woman in the dance-experience of Afrofunk as protagonist in the reinvention of being a woman (political power) in this space, as it potentiates new ways of experiencing themes such as the body, sexuality, politics and spirituality, from the incorporation of hip movements and Afrocentered meanings of dance. These new intelligibilities built by the hip shake in Afrofunk Rio, point us to the complexities of being a woman in the Brazilian context, by introducing new meanings to the woman-body and to the experiences with dance within new sociabilities for white and non-white women, configuring the rebolado as a practice that links women and as an exercise that rewrites the meanings of being a woman.